P2Y12 inhibitor monotherapy after complex percutaneous coronary intervention: a systematic review and meta-analysis of randomized clinical trials - Yohei Sotomi; Yuki Matsuoka; Shungo Hikoso; Daisaku Nakatani; Katsuki Okada; Tomoharu Dohi; Hirota Kida; Bolrathanak Oeun; Akihiro Sunaga; Taiki Sato; Tetsuhisa Kitamura; Yasushi Sakata (Scientific Reports, 2023)
Abstract It remains unknown whether the recent trend of short dual antiplatelet therapy (DAPT) followed by P2Y12 inhibitor monotherapy can simply be applied to patients undergoing complex percutaneous coronary intervention (PCI). We performed a systematic review and meta-analysis to evaluate P2Y12 inhibitor monotherapy vs. conventional DAPT in patients undergoing complex PCI and non-complex PCI (PROSPERO: CRD42022335723). Primary endpoint was the 1-year Net Adverse Clinical Event (NACE). Among 5,323 screened studies, six randomized trials fulfilled the eligibility criteria. A total of 10,588 complex PCI patients (5,269 vs. 5,319 patients) and 25,618 non-complex PCI patients (12,820 vs 12,798 patients) were randomly assigned to P2Y12 inhibitor monotherapy vs. conventional DAPT. In complex PCI patients, P2Y12 inhibitor monotherapy was associated with a lower risk of NACE than conventional DAPT [Odds ratio (OR) 0.76, 95% confidence interval (CI) 0.63–0.91, P = 0.003], whereas in non-complex PCI patients, P2Y12 inhibitor monotherapy was associated with a trend toward lowering the risk of NACE (OR 0.86, 95% CI 0.72–1.02, P = 0.09). This meta-analysis across randomized trials demonstrated that a strategy of short DAPT followed by P2Y12 inhibitor monotherapy reduces the risk of 1-year NACE in patients undergoing complex PCI.